2019
DOI: 10.1039/c9nr05719f
|View full text |Cite
|
Sign up to set email alerts
|

Towards efficient and stable perovskite solar cells employing non-hygroscopic F4-TCNQ doped TFB as the hole-transporting material

Abstract: Designing an efficient and stable hole transport layer (HTL) material is one of the essential ways to improve the performance of organic–inorganic perovskite solar cells (PSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…[ 170 ] However, spiro‐OMeTAD is expensive and has poor stability. [ 65,171 ] Also, pristine spiro‐OMeTAD has a low intrinsic charge carrier mobility; [ 65,172 ] hence, it often requires the introduction of p‐type dopants, such as tert ‐butylpyridine ( t BP), Li‐bis(trifluoromethanesulfonyl)imide (Li‐TFSI), and co‐complexes to improve its electrical conductivity. However, the corrosive and hygroscopic nature of the dopants leads to the introduction of moisture into the perovskite active layer, which subsequently reduces device performance and long‐term stability.…”
Section: Charge Transport Layersmentioning
confidence: 99%
“…[ 170 ] However, spiro‐OMeTAD is expensive and has poor stability. [ 65,171 ] Also, pristine spiro‐OMeTAD has a low intrinsic charge carrier mobility; [ 65,172 ] hence, it often requires the introduction of p‐type dopants, such as tert ‐butylpyridine ( t BP), Li‐bis(trifluoromethanesulfonyl)imide (Li‐TFSI), and co‐complexes to improve its electrical conductivity. However, the corrosive and hygroscopic nature of the dopants leads to the introduction of moisture into the perovskite active layer, which subsequently reduces device performance and long‐term stability.…”
Section: Charge Transport Layersmentioning
confidence: 99%
“…Other remarkable crosslinking approaches reported in the past two years by different groups regard the incorporation of fluorine moieties within a crosslinkable and dopant-free smallmolecule HTM to further boost hydrophobicity of the chargeextracting layer and target defect-passivating interactions with the perovskite surface, [135] the use of electropolymerization to induce in situ formation of polyamine-based dopant-free HTMs for inverted PSCs, [136] and the in situ thermal conversion of solution-processable xanthate precursors into the corresponding insoluble glycol-derivatized poly(1,4-phenylenevinylene) HTMs with different hydrophilicity profiles influencing final device performance. [137] The insertion of an interfacial layer between the perovskite and the HTM or the HTM and the top metal electrode has been shown in other cases to be advantageous for reducing charge recombination in PSCs, [138,139] also through the passivation of surface defects in the semiconductor. [140][141][142] Engineering of the perovskite/HTM interface at the molecular level has even allowed Seo and coworkers to achieve outstanding PSC performance (a PCE of 22.7%) and stability, using a pristine, undoped P3HT HTM, [143] which normally provides relatively low PCEs (10-15%, [39,144] slightly better ones if doped [145,146] ).…”
Section: Smart Htms For Pscsmentioning
confidence: 99%
“…Yield: 0. 3,3-Di[3-(9-ethylcarbazol-3-yl)carbazol-9-ylmethyl]oxetane (5). 0.4 g (0.6 mmol) of 3,3-di[3-iodocarbazol-9-yl]methyloxetane (3), 0.48 g (1.5 mmol) of 9-ethyl-9H-carbazole-3-boronic acid pinacol ester, 0.02 g (0.03 mmol) of PdCl 2 (PPh 3 ) 2 and 0.17 g (3.0 mmol) of powdered KOH were stirred in 8 mL of THF containing degassed water (1 mL) at 80 • C under nitrogen for 2 h. After TLC control the reaction mixture was cooled and quenched by the addition of ice water.…”
Section: Synthesis Of Oxetane Derivativesmentioning
confidence: 99%
“…Tremendous research efforts, which are devoted to the creation of high-power conversion efficiency PSCs, are highly related to the improved properties of newly developed hole transporting materials (HTM) [ 3 ]. Effective functions of the materials include extraction of photogenerated positive charges from a layer of perovskite, transportation of the charges to the metal electrode, and minimization of recombination losses at the TiO 2 /perovskite/HTM interface [ 4 , 5 ]. Considering the literature review, it can be concluded that spiro-OMeTAD is the best-known HTM.…”
Section: Introductionmentioning
confidence: 99%